Les professeurs d'EPS, « champions » du soutien professoral perçu par les élèves ? - Julien Moniotte; Alessandro Porrovecchio; Olivier Dieu
Rooted in self-determination theory (Deci and Ryan), our study focuses on students' perceived teacher support (TS) in different disciplines and on variables related to TS in PE. Data was collected through a questionnaire completed by 640 secondary school students. Results reveald an academic discipline effect and links between TS in PE and need of competence, grade level, enrolment in school sports association (SA). These results highlight the ability of PE teachers to create social links with their students and confirm the positive impact on the satisfaction of students' need for competence. Furthermore, the impact of the SA on perceived teacher support in PE suggests that school sport associations and other school clubs may have a positive impact on the social bond between students and their teachers.